2022
DOI: 10.21203/rs.3.rs-1431715/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness and safety of inactivated SARS-CoV2 vaccine (BBIBP-CorV) among healthcare workers: A seven-month follow-up study at fifteen hospitals

Abstract: OBJECTIVE Health care workers_ the first line army in the current pandemic_ are the most vulnerable group for COVID-19 infection. Vaccination of health care workers is strongly recommended to salvage our army. However, more research is needed to determine the safest and most effective vaccine. In our study, we assessed the safety and effectiveness of the first approved vaccine in Egypt_ the Sinopharm vaccine. DESIGN, SETTING: An ambispective cohort study was conducted in fifteen triage and isolation hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…6 Our study is one of few studies globally to evaluate VE of primary series BBIBP-CorV against symptomatic infection during the Delta period [6]. Our finding of 40% VE was in the range of primary series BBIBP-CorV VE against symptomatic infection during Delta described in two studies from China, which found aVE of 50% (95%CI: 4; -74) [18] and 75 (95%CI: 6; -94) [19], and one study from Egypt, that found VE of 67% (95%CI: 43; 80) [20]. Studies of BBIBP-CoRV against more severe outcomes have shown mixed results, but have consistently shown the added benefit of booster doses, mostly against Delta but also against Omicron; a study of primary series BBIBP-CorV VE against hospitalization among people aged 18-64 years old in Hungary during Delta found a VE of 54% (44; 62) in the 14-120 days following the second dose that decreased over time, but increased to 77-95% following homologous or heterologous booster [21]; for 65-100 year-olds, the same study found slightly lower VE against hospitalization with similar trends following booster doses.…”
Section: Discussionsupporting
confidence: 59%
“…6 Our study is one of few studies globally to evaluate VE of primary series BBIBP-CorV against symptomatic infection during the Delta period [6]. Our finding of 40% VE was in the range of primary series BBIBP-CorV VE against symptomatic infection during Delta described in two studies from China, which found aVE of 50% (95%CI: 4; -74) [18] and 75 (95%CI: 6; -94) [19], and one study from Egypt, that found VE of 67% (95%CI: 43; 80) [20]. Studies of BBIBP-CoRV against more severe outcomes have shown mixed results, but have consistently shown the added benefit of booster doses, mostly against Delta but also against Omicron; a study of primary series BBIBP-CorV VE against hospitalization among people aged 18-64 years old in Hungary during Delta found a VE of 54% (44; 62) in the 14-120 days following the second dose that decreased over time, but increased to 77-95% following homologous or heterologous booster [21]; for 65-100 year-olds, the same study found slightly lower VE against hospitalization with similar trends following booster doses.…”
Section: Discussionsupporting
confidence: 59%
“…An ambispective cohort study assessing VE of BBIBP-CorV (Sinopharm) against COVID-19-related ICU admission among healthcare workers across Egypt, and a study from Hungary (HUN-VE 3) estimating effectiveness of six different vaccine types, including BBIBP-CorV (Sinopharm) and ChAdOx1 nCoV-2 against COVID-19-related hospitalisation and death, both reported more modest BBIBP-CorV (Sinopharm) VE estimates during a period of delta variant transmission, compared to other studies [15][16][17][18][19][20]. These were reported as an overall adjusted VE of 65% and 45.7% against hospitalisation in studies from Egypt and Hungary, respectively, and 58.6% against COVID-19-related death in the study from Hungary [15,21]. To our knowledge, our study is the third to report on BBIBP-CorV (Sinopharm) effectiveness data within the context of a delta variant…”
Section: Plos Onementioning
confidence: 77%
“…and 100% effective in preventing moderate and severe disease. 21 Vaccination efforts currently underway all over the world are the most important weapon in our arsenal against the COVID-19 pandemic. A number of different vaccines have been developed in different areas of the world.…”
Section: Discussionmentioning
confidence: 99%